Açaí (Euterpe oleracea Mart.) Seed Oil Exerts a Cytotoxic Role over Colorectal Cancer Cells: Insights of Annexin A2 Regulation and Molecular Modeling - da Silva, Marcos Antonio Custódio Neto; Tessmann, Josiane Weber; Borges, Kátia Regina Assunção; Wolff, Laís Araújo Souza; Botelho, Fernanda Diniz; Vieira, Leandro Alegria; Morgado-Diaz, Jose Andres; Franca, Tanos Celmar Costa; Barbosa, Maria do Carmo Lacerda; Nascimento, Maria do Desterro Soares Brandão; Rocha, Murilo Ramos; de Carvalho, João Ernesto (Metabolites, 2023)
Açaí, Euterpe oleracea Mart., is a native plant from the Amazonian and is rich in several phytochemicals with anti-tumor activities. The aim was to analyze the effects of açaí seed oil on colorectal adenocarcinoma (ADC) cells. In vitro analyses were performed on CACO-2, HCT-116, and HT-29 cell lines. The strains were treated with açaí seed oil for 24, 48, and 72 h, and cell viability, death, and morphology were analyzed. Molecular docking was performed to evaluate the interaction between the major compounds in açaí seed oil and Annexin A2. The viability assay showed the cytotoxic effect of the oil in colorectal adenocarcinoma cells. Acai seed oil induced increased apoptosis in CACO-2 and HCT-116 cells and interfered with the cell cycle. Western blotting showed an increased expression of LC3-B, suggestive of autophagy, and Annexin A2, an apoptosis regulatory protein. Molecular docking confirmed the interaction of major fatty acids with Annexin A2, suggesting a role of açaí seed oil in modulating Annexin A2 expression in these cancer cell lines. Our results suggest the anti-tumor potential of açaí seed oil in colorectal adenocarcinoma cells and contribute to the development of an active drug from a known natural product.
Keywords: polyphenols; Annexin A2; autophagy; Euterpe oleracea Mart.; apoptosis